Nandi Mandapa (pillared hall) facing the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is the Nandi mandapa (pillared hall) facing the Mahanaleshwar Temple. It is an open mandapa consisting of a plinth with four pillars on its corners that support a canopy shikhara (superstructure). Nandi is facing the garbhagriha (sanctum sanctorum) of the temple. The sculpture is decked with jewels.